Fundamentals and Scientific Challenges in Structural Design of Cathode Materials for Zinc‐Ion Hybrid Supercapacitors. Issue 3 (2nd December 2022) - Javed, Muhammad Sufyan; Najam, Tayyaba; Hussain, Iftikhar; Idrees, Muhammad; Ahmad, Awais; Imran, Muhammad; Shah, Syed Shoaib Ahmad; Luque, Rafael; Han, Weihua
Abstract: One of the most exciting new developments in energy storage technology is Zn‐ion hybrid supercapacitors (ZHSCs). ZHSCs combine Zn‐ion batteries with supercapacitors (SCs) to address the energy and power needs of portable devices and electric automobiles. Low energy density and the development of cathode material are significant issues for ZHSCs. This review provides an in‐depth investigation of charge storage mechanisms from SCs to ZHSCs. The advantages/disadvantages of ZHSCs, the recent development of cathode materials, and the new design for device fabrications are critically summarized. New cathode materials should be developed to achieve high energy density while preserving the inherent power capability and stability. People increasingly engage with smart electronic and hybrid gadgets, demanding flexible, resilient, and highly safe energy storage devices. ZHSC has emerged as a complete alternative to risky sodium‐ion/lithium‐ion technologies. An overview of all reported carbon‐based, biomass‐derived carbons, metal oxides, MOFs, COFs, MXenes, graphene, and composite materials employed for ZHSCs is comprehensively provided. Furthermore, cathode materials for flexible, micro, wire‐shaped, printed, and photo‐rechargeable ZHSCs are also examined with their practical challenges. This review is anticipated to offer valuable recommendations for designing and manipulating cathode materials for high‐performance ZHSCs to achieve real‐world applications. Abstract : This review article presents an in‐depth investigation of charge storage mechanisms of cathode materials for Zn‐ion hybrid supercapacitors, challenges and future prospects.